2016
DOI: 10.1136/jnnp-2016-314991
|View full text |Cite
|
Sign up to set email alerts
|

Chronic neuropathic pain severity is determined by lesion level in aquaporin 4-antibody-positive myelitis

Abstract: Persistent, caudally located (ie, thoracic) cord lesions in AQP4-Ab-positive patients associate with high postmyelitis chronic pain scores, irrespective of number of myelitis relapses, lesion length and lesion burden. Although disability correlated with pain in isolation, it became an insignificant predictor of pain when analysed alongside craniocaudal location of lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 14 publications
4
36
2
Order By: Relevance
“…### p < 0.001 vs. control group, ***p < 0.01, vs. SCI group and vehicle, $ p < 0.05, $$$ p < 0.001 vs. laser group. ¥¥¥ p < 0.001 vs. hADSc group studies showed the upregulation of AQP4 could also lead to neuropathic pain [68][69][70][71]. In the present study, AQP4 expression is significantly increased in SCI group.…”
Section: Discussionsupporting
confidence: 51%
“…### p < 0.001 vs. control group, ***p < 0.01, vs. SCI group and vehicle, $ p < 0.05, $$$ p < 0.001 vs. laser group. ¥¥¥ p < 0.001 vs. hADSc group studies showed the upregulation of AQP4 could also lead to neuropathic pain [68][69][70][71]. In the present study, AQP4 expression is significantly increased in SCI group.…”
Section: Discussionsupporting
confidence: 51%
“…A previous study reported a similar incidence of fatigue in NMOSD and MS patients, with a strong correlation between depression and fatigue [9]. On the other hand, chronic pain is a common symptom causing deterioration of activities of the daily living in patients with MS and NMOSD [15][16][17]. However, the relationship between fatigue and pain has not been fully investigated, particularly in NMOSD patients.…”
Section: Introductionmentioning
confidence: 96%
“…Expression of the water channel aquaporin-4 (AQP4) is induced in spinal cord astrocytes after spinal cord injury in rats 51 and nerve injury in humans 108 . The specific role of AQP4 in animal models of neuropathic pain remains to be determined.…”
Section: Introductionmentioning
confidence: 99%